Non-alcoholic fatty liver disease in patients with hypothyroidism presenting at a rural tertiary care centre in north India. (April 2021) - Grewal, Harpreet; Joshi, Sandeep; Sharma, Ruby; Mittal, Puneet; Goel, Ankur
Apart from its association with metabolic syndrome and diabetes mellitus, non-alcoholic fatty liver disease (NAFLD) has been thought to be linked with other endocrine and metabolic disorders. Recent data suggest that hypothyroidism may be a significant risk factor for development and progression of NAFLD. The present study was conducted to evaluate the presence of NAFLD in patients with hypothyroidism presenting to a rural tertiary care centre in north India. The diagnosis of NAFLD was made on the basis of radiological findings and derangement of liver enzymes. Our findings showed that ultrasonographic evidence of fatty liver as well as increase in the serum transaminase level above normal range were significantly higher in hypothyroidism patients as compared with controls. On multivariate regression analysis of the patients' data, the presence of hypothyroidism was independently associated with risk of NAFLD. We therefore conclude that hypothyroidism is a significant independent risk factor.